Strategic doing : ten skills for agile leadership - Morrison, Edward (John Wiley & Sons, Inc., 2019)
Ten skills for agile leadership Complex challenges are all around us-they impact our companies, our communities, and our planet. This complexity and the emergence of networks is changing the practice of strategic management. Today's leaders need to understand how to design and guide complex collaborations to accelerate innovation and change-collaborations that cross boundaries both inside and outside organizations. Strategic Doing introduces you to the new disciplines of agile strategy and collaborative leadership. You'll learn how to design and guide complex collaborations by following a discipline of simple rules that you won't find anywhere else. - Unleash the power of true collaboration - Learn and master the 10 skills of agile leadership - Apply individual skills to targeted situations - Introduces a new discipline of leadership strategy Filled with compelling case studies, Strategic Doing outlines a new discipline of leadership strategy specifically designed for open, loosely-connected networks.